Resolução PRES nº 1, de 8 de janeiro de 2007 - Andre Carlos de Amorim Pimentel Filho; Carlos Fernando Mazzoco; Carlos Vinicius Soares Cabeleira; Elisandra de Oliveira Olimpio; Fabricio Caser; Frederico Lugon Nobre; Helder Magno da Silva; Jose Nilso de Lirio; Luciana Furtado de Moraes; Luciana Loureiro de Oliveira; Nadja Machado Botelho; Paulo Roberto Berenger Alves Carneiro; et al. (BSMPF, Brasília, DF, p. 11, 1. quinzena jan. 2007., 2007)
Dispõe sobre a atribuição dos Ofícios da Procuradoria da República no Espírito Santo.